New Literature from the Paris Disputation against the Talmud: The Text of Vat. lat. 822 (fols. 204ra–205ra) and Its Reliance on the Tradition of the Errores Iudaeorum - Lampurlanés, Isaac (Medieval encounters, 2024)
In 1239, the convert Nicholas Donin submitted thirty-five articles against the Talmud to Pope Gregory IX. As a result, Christendom became aware of how Jews observed an oral law that was allegedly plagued with folly, blasphemy, and heresy. This triggered the infamous trial against the Talmud and resulted in the production of several Latin translations of rabbinical texts, including the compilation of the Extractiones de Talmud (1245). The present article mainly focusses on a short text taken from the manuscript Vatican City, Biblioteca Apostolica Vaticana, MS Vat. lat. 822 (folios 204ra–205ra), which includes a series of Talmudic passages that derive from texts which emerged from the Paris Disputation against the Talmud (1240–1245). From it, we are able to infer new information regarding the genesis of subsequent anti-Jewish works, including the Errores Iudaeorum by Thibaud de Sézanne and Passau Anonymous anti-Jewish sections. Additionally, we also provide the edition and translation of the text of the Vatican manuscript at the end of the article.